Respuesta :
Answer:
6u+7u-16=-81
We simplify the equation to the form, which is simple to understand
6u+7u-16=-81
We move all terms containing u to the left and all other terms to the right.
+6u+7u=-81+16
We simplify left and right side of the equation.
+13u=-65
We divide both sides of the equation by 13 to get u.
u=-5
Step-by-step explanation:
I think i did it correct
Answer:
-5
Step-by-step explanation:
6u+7u-16=-81
Carry over the "-16" and make "u" the subject.
6u+7u= -81+16
13u= -65
Carry over the "13" and make "u" the subject
u= -65/13
u= - 5